عبداللہ حسین کی ناولٹ نگاری:دیہی اور شہری زندگی کے تناظر میں - Abdul Ghafoor; Dr. Wahidur Rehman Khan (Khayaban - خیابان, 2021)
Abdullah Hussain is one of the brightest stars of Urdu fiction. His creations are a milestone in the history of urdu fiction. His novels and novelettes have gained special attention. He has presented ups and down of life in his stories with a masterly skill. He has portrayed the real pictures of traditions, beliefs and norms of the social life in his writtings. It is interesting that all the rhetoric of modern and ancient values is presented in his novels, novelletes and short stories. He has presented the main element of rural and urban life very well in his stories. Abdullah Hussain's novellets have been viewed here in the subject matter under discussion on urban and rural perspectives.